Experimental demonstration of quantum effects in the operation of microscopic heat engines - Klatzow, J; Becker, J; Ledingham, P; Weinzetl, C; Kaczmarek, K; Saunders, D; Nunn, J; Walmsley, I; Uzdin, R; Poem, E (American Physical Society, 2019)
The ability of the internal states of a working fluid to be in a coherent superposition is one of the basic properties of a quantum heat engine. It was recently predicted that in the regime of small engine action, this ability can enable a quantum heat engine to produce more power than any equivalent classical heat engine. It was also predicted that in the same regime, the presence of such internal coherence causes different types of quantum heat engines to become thermodynamically equivalent. Here, we use an ensemble of nitrogen vacancy centers in diamond for implementing two types of quantum heat engines, and experimentally observe both effects.